Using established occupational respiratory cancer risk factors for assessing the internal validity in an unmatched case-control study in the Campania Region of Italy, 1988-1990 - Soskolne, Colin L.; Jhangri, Gian S.; Pagano, Giovanni; Botte, Gerardo; Di Cintio, Patrizia; Cardarelli - Acid Study Group, Pascale (European Journal of Oncology and Environmental Health, 2017)
Background. It is important to ensure the validity of softer epidemiological data such as occupational histories. Validation of the larger case-control study, on the well-established confounders of tobacco and alcohol consumption and from which the present dataset derives, has strongly supported the utility of our dataset. As a further step in validating our dataset, we examined the specificity of several workplace risk factors in relation to respiratory tract cancers. Aim. The purpose of the paper is to determine whether classical risk factors, as well as those of acid mists, for various respiratory tract cancers could be corroborated in our dataset. Patients and methods. Using unconditional logistic regression, and controlling the effects of age, tobacco and alcohol consumption, we examined the association between numerous occupational exposures and respiratory tract cancers as part of an extensive occupational cancer case-control study of 513 male hospitalized patients in the Campania Region of Italy. Our dataset for this sub-study included exposure in formation on up to 20 major groups of workplace chemicals, with the target cancers of the lung (n = 111), the larynx (n = 35), and the naso/nasal/pharynx (n = 22), for a total of 168 respiratory tract cancer cases. Each of the specific respiratory tract case groupings was compared with 247 other unmatched patients without any of these cancers or oral cavity cancers, including patients having any other reason for hospitalization. Results. The results demonstrate statistically significant associations between established occupational exposures (asbestos/lime/cement, dyes, acids and welding fumes) and respiratory tract cancers. Discussion. Our findings are consistent with the literature. The finding of a statistically significant association between acid exposure and lung cancer (OR = 3.84) warrants replication through other studies; a non-significant, but elevated association between acid exposure and laryngeal cancer (OR = 2.18), consistent with the recent literature, might be because of low statistical power. Conclusion. Corroborative trends in established findings add credibility to the dataset for exploring more deeply the hypothesis of an acid association with bladder cancer.